2004
DOI: 10.1111/j.1399-3089.2004.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to deplete anti‐Galα1‐3Gal antibodies after pig‐to‐baboon organ xenotransplantation by immunoaffinity columns containing multiple Galα1‐3Gal oligosaccharides

Abstract: The EIA reduces anti-alphaGal and APHA antibodies, preventing the HAR of non-transgenic pig hearts transplanted in baboons, as does hDAF expression. However, EIA does not modify the level of anti-alphaGal IgM and APHA antibodies after Tx nor the AHXR of either non-transgenic or hDAF pig organs. The increase in anti-alphaGal IgM after Tx was similar for the different antibodies of the anti-alphaGal polymorphism, and was only partially neutralized in vitro with the specific alphaGal oligosaccharide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Approaches to eliminate antiporcine antibodies in pigto-primate transplantation have included plasmapheresis (34), extracorporal immunoabsorption of immunoglobulins (35), or selective extracorporal immunophoresis removing antipig (36), or anti-␣-Gal antibodies (3,31,32). The effects, however, were transient since antibodies are continuously produced and were associated with complications (15).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Approaches to eliminate antiporcine antibodies in pigto-primate transplantation have included plasmapheresis (34), extracorporal immunoabsorption of immunoglobulins (35), or selective extracorporal immunophoresis removing antipig (36), or anti-␣-Gal antibodies (3,31,32). The effects, however, were transient since antibodies are continuously produced and were associated with complications (15).…”
Section: Discussionmentioning
confidence: 95%
“…Primates have a polymorphism of the anti-␣-Gal antibody population against ␣-Gal disaccharides, trisaccharides one, two, and six and pentasaccharides (30). Columns containing multiple ␣-Gal oligosaccharides have been applied in xenotransplantation with moderate success (31,32). More complete removal of ␣-Gal antibodies was achieved when two different polymers were combined in a column, suggesting that a combination of additional polymers carrying different ␣-Gal structures may be more effective in antibody absorption (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study of immunosuppressed cynomolgus monkey recipients of cardiac xenografts, Lam and colleagues could demonstrate a considerable increase of both IgM and IgG anti-non-αGal antibodies in all animals with AHXR in the graft, whilst no relevant changes in the titers were shown in animals that did not reject their transplant [78]. In another series, it was shown that repeated extracorporeal immunoadsorptions, using an αGal column containing disaccharides, type 2 trisaccharides and pentasaccharides failed to deplete antiαGal antibodies in baboon recipients of a porcine xenograft [97]. Similarly, Buhler and colleagues could show that exposure of baboons to porcine antigens resulted in the production of anti-αGal and anti-non-αGal antibodies [39].…”
Section: The Elicited Xenoreactive Immune Responsementioning
confidence: 92%
“…Manez et al [6] demonstrated that extracorporeal immunoadsorption of anti-Gal antibodies in baboons, using immunoaffinity columns containing various Gal oligosaccharides, reduced anti-Gal antibody levels and prevented hyperacute rejection. The level of anti-Gal immunoglobulin M after nontransgenic or hDAF pig heart transplantation was not significantly modified, however, nor was the occurrence of AHXR.…”
Section: Heart Transplantsmentioning
confidence: 98%